Human B19 parvovirus infetion: an example of multiple pathogenic effects determined by differences in host susceptibility - Philip P. Mortimer (Memorias do Instituto Oswaldo Cruz, 1992)
B19 infection offers some general lessons about human viruses and their possible effects on the human host, as follows: (1) Ubiquitous apparently benign viruses may have severe effects on a compromissed host. The virus may be invariable but the host can have diverse susceptibilities. (2) B19 and some other human viruses (through for none is the evidence so clear as for B19) have narrowly targetted effects. The host cell of B19 is a specialised progenitor of mature red cells: impairment of the function of this cell by B19 may cause profound anaemia. (3) The 'normal'host response to B19 may also cause disease, though this is slef limiting. (4) The effects of malfunction of the virus'target cell are exacerbated when the immune response is impaired by congenital or acquired immunodeficiency, immunosupressive therapy or, in the case of the fetus, developmental immaturity that allows the virus to persist.